2017
DOI: 10.1001/jamacardio.2016.4954
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention With Bioresorbable Scaffolds in a Young Child

Abstract: To our knowledge, this is the first report of PCI with BRSs in a child. This represents an application of a BRS with potentially important implications for the future treatment of coronary artery disease in children and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…On histology, substantial strut coverage with neointima was seen. 29 Taken together these data suggest that the concept of BRS -full bioresorption after fulfilling the role of scaffolding -is potentially applicable for the treatment of pediatric patients. 30 It should be noted, however, that the application of BRS technology in pediatric patients will be acceptable once the concerns of long-term safety are eliminated and the applicability for a small vessel is confirmed.…”
Section: Current Role Of the Absorb Scaffold And Future Implicationsmentioning
confidence: 84%
“…On histology, substantial strut coverage with neointima was seen. 29 Taken together these data suggest that the concept of BRS -full bioresorption after fulfilling the role of scaffolding -is potentially applicable for the treatment of pediatric patients. 30 It should be noted, however, that the application of BRS technology in pediatric patients will be acceptable once the concerns of long-term safety are eliminated and the applicability for a small vessel is confirmed.…”
Section: Current Role Of the Absorb Scaffold And Future Implicationsmentioning
confidence: 84%
“…Percutaneous treatment of atherosclerotic coronary artery disease in the pediatric population with FH is found in the literature only as case reports. In such a case report, Nazif et al (9) reported the successful treatment of a 3-year-old patient with PCI using a bioresorbable scaffold (BRS). Their patient had LMCA and RCA osteal critical stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bilal et al (10) described a 12-year-old child with HoFH that underwent triple coronary bypass. In a recently published paper, Nazif et al (13) presented a 3-year-old boy with HoFH and severe CAD, and the case was managed with PCI with bioresorbable scaffolds for the first time. CABG between LIMA and LAD was established in our case because of the involvement of multiple vessels and ischemic symptoms.…”
Section: Discussionmentioning
confidence: 99%